Genomic organization and sequence dynamics of the AvrPiz-t locus in Magnaporthe oryzae - Li, Ping (Zhejiang University Press, 2012)

(untitled)
Plants utilize multiple layers of defense mechanisms to fight against the invasion of diverse pathogens. The R gene mediates resistance, in most cases, dependent on the co-existence of its cognate pathogen-derived avirulence (Avr) gene. The rice blast R gene Piz-t corresponds in gene-for-gene fashion to the Magnaporthe oryzae Avr gene AvrPiz-t. In this study, we determined and compared the genomic sequences surrounding the AvrPiz-t gene in both avirulent and virulent isolates, designating as AvrPiz-t-ZB15 and avrPiz-t-70-15 regions, respectively. The sequence of the AvrPiz-t-ZB15 region is 120 966 bp whereas avrPiz-t-70-15 is 146 292 bp in length. The extreme sequence similarity and good synteny in gene order and content along with the absence of two predicted genes in the avrPiz-t-70-15 region were observed in the predicted protein-coding regions in the AvrPiz-t locus. Nevertheless, frequent presence/absence and highly dynamic organization of transposable elements (TEs) were identified, representing the major variation of the AvrPiz-t locus between different isolates. Moreover, TEs constitute 27.3% and 43.2% of the genomic contents of the AvrPiz-t-ZB15 and avrPiz-t-70-15 regions, respectively, indicating that TEs contribute largely to the organization and evolution of AvrPiz-t locus. The findings of this study suggest that M. oryzae could benefit in an evolutionary sense from the presence of active TEs in genes conferring avirulence and provide an ability to rapidly change and thus to overcome host R genes.